NILAI-NILAI PENDIDIKAN DANKONSERVASI LINGKUNGAN HIDUPDALAM ISLAM - Fatah, Ahmad (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2018)
Abstract: This study aims to discuss the value of education and environmental conservation in the Islamic view. The discussion of environmental conservation is factual and contextual. This will be more interesting if viewed from the view of Islam. The environment in Islam with variants pivots the awareness that everything is God's and should be used for the purposes that God has set forth. This is indeed the essence of the manifestation of a servant's gratitude towards the favors given by the creator. Man as the holder of the mandate (khalîfah Allâh fî al-ardh) is commanded to use the mandate of the management of the earth and its contents in the framework of obedience to Allah subhanahu wata'ala. Keywords:Value Of Education, Environmental Conservation, Islam.